Siak River Aquatic Hub Di Pekanbaru Dengan Pendekatan Prinsip Desain Santiago Calatrava - Yaasin Ali Akbar; Mira Dharma Susilawaty; Yohannes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The lack of knowledge how human relation with aquatic occur in Pekanbaru society. They have need a place to introduce aquatic in order to growing concern for aquatic at oncegood for human pyshcology and to reduce stress. Siak River Aquatic Hub is a place which giving education about aquatic a live by sub-diving, marine breeding, aquaplants conservation, touching marine and art by aquatic. Water as the main element of design implemented in concept transformation as nature section and high-tech structure making theiconic building in Pekanbaru all of those can be realized by Santiago Calatrava design principle. As Calatrava to interested user by having nature in design so make the Diving Soulto Realms is a good main concept. The main idea of Siak River Aquatic Hub are bring user’s soul to feel how aquatic life and be clarified by profile of Siak River as familiar nature inPekanbaru and be transformationed by Calatrava design principle heed by water reflector, high-tech of structure and a lot of cuvring applied in Siak River Aquatic Hub.Keywords : Aquatic Hub, Sungai Siak, Calatrava.